RESEARCH AND STUDY THROUGH THE INTERNET OF THINGS (IOT) ON THE BENEFITS OF ORGANIC FERTILIZERS TO THE SOIL HEALTH AND INCREASE IN CROP PRODUCTION AS COMPARED TO CHEMICAL FERTILIZERS - Sondhiya, Ritu Raj; Singh, Vikash Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The growing emphasis on sustainable agriculture has made the comparison of organic and chemical fertilizers within the context of soil enrichment and crop yield improvement a vital subject of study very important. Internet of Things (IoT) technology enables this study to fully evaluate the effectiveness of conventional and organic fertilisers. In agricultural settings, we installed a network of IoT sensors to monitor crop development indicators and significant soil parameters like pH, moisture content, and nutrient levels. We examined the data to see how various kinds of fertiliser influenced harvest success and soil condition. Our findings show that whilst chemical fertilisers produce greater initial crop yields and fast nutrient availability, organic fertilisers help to maintain soil health and sustainable output over time. The IoT enabled approach helps one to better grasp the dynamics of fertiliser application and their effects on agricultural output. This paper emphasises the possibilities of IoT technology to enhance agricultural practices by means of well-informed decision-making, therefore enhancing food production productivity and sustainability.